Pengaruh Kompensasi Terhadap Kepuasan Kerja Dengan Motivasi Sebagai Variabel Intervening Pada PT Arena Tiket Indonesia Di Yogyakarta - mira permaisuri (JURNAL EKOBIS DEWANTARA, 2018)
Abstract This study aims to analyze the effect of compensation on motivation, the influence of motivation on job satisfaction, the effect of compensation on job satisfaction and the effect of compensation on job satisfaction with motivation as intervening variable at PT Arena Tiket Indonesia in Yogyakarta.The nature of research is correlational research. The population in this research is all employees of PT Arena Tiket Indonesia in Yogyakarta. The sample of the study was 45 people. Data collection method used questionnaire method, while data analysis technique used multiple regression analysis supported by F test, T test and path path and classical assumption test consisting of normality test, multicollinearity test, and heterokedastisity test.The result of the research with the significance level of 5% or 0.05 indicates that the compensation (X) has no significant effect on the motivation (Z) (0.956> 0.05), the motivation has no significant effect on Job Satisfaction (0.256> 0.05) compensation (X) has significant effect on Job Satisfaction (0,045 <0,05) and compensation has positive and significant effect to job satisfaction but not motivation as variluel intervening (0,059> 0,05).